Perkembangan Objek Wisata Pura Uluwatu Bali - Gagih Pradini; Dipa Teruna Awaloedin; Anisa Putri Kusumaningrum; Putri Aulia Ardani; Emilio Angga (Jurnal Ilmiah Wahana Pendidikan, 2023)
Pura Luhur Uluwatu or Uluwatu Temple is located in Pecatu Village, Kuta District, Badung Regency, Bali. Uluwatu Temple, also called Luwur Temple, is one of the six Sad Kahyangan temples, the main spiritual pillars located on the island of Bali. Piodalan or ceremony commemorating the founding of the Temple is held on Anggara Kasih day, in Wuku Medangsia in Caka calendar. This ceremony usually lasts for three days attended by thousands of Hindus, Pura Luhur Uluwatu is one of the best places in Bali to see the sunset, with views directly overlooking the Indian Ocean. Without a doubt, what makes Uluwatu Temple even more beautiful is the 250-foot cliff above the waves of the Indian Ocean. A small forest is located around Uluwatu and hundreds of herds of monkeys live there. Who is believed to be the guardian of the purity of the area. Uluwatu Kecak dance or Fire Dance has a unique music or tone. A dance accompanied by human voices and rattles as well as the voices of dozens of people, the Kecak dance or "Cak" dance or Fire Dance actually departs from the Sang Hyang ceremony, a traditional ritual tradition where dancers meet with the gods. Or the spirits of ancestors will be in an unconscious state when communicating.